2020
DOI: 10.1016/j.meegid.2020.104438
|View full text |Cite
|
Sign up to set email alerts
|

Gene signatures of SARS-CoV/SARS-CoV-2-infected ferret lungs in short- and long-term models

Abstract: Coronaviruses (CoVs) consist of six strains, and the severe acute respiratory syndrome coronavirus (SARS-CoV), newly found coronavirus (SARS-CoV-2) has rapidly spread leading to a global outbreak. The ferret ( Mustela putorius furo) serves as a useful animal model for studying SARS-CoV/SARS-CoV-2 infection and developing therapeutic strategies. A holistic approach for distinguishing differences in gene signatures during disease progression is lacking. The present study discovered gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 66 publications
0
44
0
1
Order By: Relevance
“…The top 10% highly differentially expressed genes in SARS-CoV-/SARS-CoV-2-infected groups relative to mock-infected controls were computed as previously described. [ 22 – 24 ] Both P values < .05 and adjusted false discovery rates were utilized to screen for significantly different genes. The final gene lists were uploaded to the GO Elite platform for constructing biological networks, processes, and diseases using the Database for Annotation, Visualization, and Integrated Discover version.…”
Section: Methodsmentioning
confidence: 99%
“…The top 10% highly differentially expressed genes in SARS-CoV-/SARS-CoV-2-infected groups relative to mock-infected controls were computed as previously described. [ 22 – 24 ] Both P values < .05 and adjusted false discovery rates were utilized to screen for significantly different genes. The final gene lists were uploaded to the GO Elite platform for constructing biological networks, processes, and diseases using the Database for Annotation, Visualization, and Integrated Discover version.…”
Section: Methodsmentioning
confidence: 99%
“…Based on its susceptibility, the ferret model has been used to assess a number of FDA-approved drugs, which have been suggested as antiviral candidates against SARS-CoV-2 and yielded results that may help facilitate the selection of antiviral treatments for COVID-19 (106). In addition, alteration of gene expression in short-and long-term-infected ferrets has been shown using bioinformatics approaches: During the course of infection, the stemness, development, and Wnt-and cytoskeleton remodeling-related pathways mainly change in the early phase of lung infection, while the ECM, immune response, G protein-coupled receptor, and cell adhesion-related pathways are affected in the later phase (107). Given the rapid spreading of SARS-CoV-2 in humans, ferrets can be a useful model for understanding COVID-19 transmission dynamics.…”
Section: Ferretmentioning
confidence: 99%
“…Because these clinically approved drugs inhibit, via RhoA/ actin pathway, macrophage movement, and expression of macrophage receptors, they have also a potential to inhibit ACE2 receptors expression and the recruitment of macrophages to the lungs of the COVId-19 patients, which in turn would decrease cytokine storm and attenuate ARDS. This hypothesis is also supported by the recent Through Gene Ontology (GO) and MetaCore analyses of gene expression profile in the SARS-CoV/SARS-CoV-2 infection ( Liu et al., 2020 ). These analyses showed that the upregulation of actin/cytoskeleton remodeling/cell migration pathways is crucial for the SARS-CoV-2 infection.…”
mentioning
confidence: 69%